2020
DOI: 10.1177/0961203319897116
|View full text |Cite
|
Sign up to set email alerts
|

Endomyocardial biopsies in the diagnosis of myocardial involvement in systemic lupus erythematosus

Abstract: Background Endomyocardial biopsy (EMB) is considered the gold standard for diagnosing myocardial involvement in most inflammatory conditions, including systemic lupus erythematosus (SLE). However, EMBs are rarely performed, and most of the myocardial histopathology reports in SLE consist of postmortem data. We therefore sought to describe the histopathologic findings of contemporary EMBs in SLE performed in clinical practice. Methods A retrospective review of histopathology reports from SLE patients who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Second, the etiological heterogeneity of the study population confers some limitations to our research. Nevertheless, myocardial fibrosis is a common feature on cardiac pathology in patients with SLE ( 6 ), IIM ( 40 ), SS ( 41 ), and SSc ( 2 ). The shared pathophysiologic mechanisms of myocardial involvement in AIDs, such as immune complex deposition and chronic cumulative inflammation, may account for the commonality across imaging findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the etiological heterogeneity of the study population confers some limitations to our research. Nevertheless, myocardial fibrosis is a common feature on cardiac pathology in patients with SLE ( 6 ), IIM ( 40 ), SS ( 41 ), and SSc ( 2 ). The shared pathophysiologic mechanisms of myocardial involvement in AIDs, such as immune complex deposition and chronic cumulative inflammation, may account for the commonality across imaging findings.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, histopathological studies have demonstrated that myocardial fibrosis is prevalent in AIDs and indicates impaired cardiac function ( 2 , 5 ). For instance, a high frequency (90%) of interstitial fibrosis in myocardium occurred in patients with systemic lupus erythematosus (SLE) based on endomyocardial biopsy ( 6 ). Although endomyocardial biopsy is the gold standard for the diagnosis of myocardial involvement, its invasive properties and complications sometimes limit its clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…We could also appreciate a microscopical observation of fibrosis and vasculitis at the myometrium. Interstitial fibrosis to myocardial involvement [ 15 ] and gynecological vasculitis in SLE have been reported to date [ 16 ], causing activating the complement cascade to damage the microvascular structure of the uterus. In particular, our patient had repeated paralytic ileus and lupus enteritis without steroid treatment for one year.…”
Section: Discussionmentioning
confidence: 99%
“…This patient had 2 separate endomyocardial biopsies: neither of which revealed the classic inflammatory infiltrate in association with myocyte degeneration ( 3 ). In the most contemporary published series of endomyocardial biopsies of serology-proven lupus patients with decreased LVEF, none of the relevant samples had features characteristic for lupus myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…In the most contemporary published series of endomyocardial biopsies of serology-proven lupus patients with decreased LVEF, none of the relevant samples had features characteristic for lupus myocarditis. Findings included interstitial fibrosis, myocyte hypertrophy, and mild lymphocytic and macrophage infiltration without clear evidence of myocarditis ( 3 ). Therefore, there is growing evidence that CMR imaging with late gadolinium enhancement may be a better diagnostic modality for lupus myocarditis ( 4 ).…”
Section: Discussionmentioning
confidence: 99%